(untitled) (Terr@ Plural, 2022)
This work aims to characterize the use and occupation of land in rural settlements in the Midwest region of Brazil through remote sensing indexes and the use of free software. We applied NDVI and NDWI indexes employing the software QGIS (QGIS Development Team, 2015) and using 2014 Landsat images (USGS, 2015). We defined five classes of interest: urban, agricultural, livestock, grasses and trees, and forests. For NDVI, the classes were reclassified according to the values obtained in the vegetation cover samples in each study area. Easy to use, the tools enable studies to identify and measure areas of agricultural production, as well as environmental analysis. In addition, it should be emphasized that technologies here employed can be used with images from different periods, since the indexes allow to record the changes in the soil use and in the environmental quality. So, it allows to verify the evolution of the occupation and soil use.